2012
DOI: 10.1093/ejcts/ezs257
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative pulmonary rehabilitation in patients with lung cancer and chronic obstructive pulmonary disease

Abstract: A 4 to 6-week PPR programme prepares the NSCLC and COPD patients properly for the surgical approach, reducing the functional limitations of inoperability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 20 publications
2
47
0
6
Order By: Relevance
“…In recent years, numerous studies have investigated the relevance of pulmonary rehabilitation, mostly in patients with Chronic Obstructive Pulmonary Disease (COPD), and subsequent improvement in quality of life, decreased dyspnea and lower risk of hospitalization (8). To a lesser extent, work is being carried out on the value of a prehabilitation program in preparation for pulmonary surgery with a view to improving physical fitness and limiting postoperative respiratory disability (9). The review published by Nagarajan et al concluded that prehabilitation (PR) for pulmonary surgery improved exercise functional capacity and limited postoperative lung capacity reduction (10).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, numerous studies have investigated the relevance of pulmonary rehabilitation, mostly in patients with Chronic Obstructive Pulmonary Disease (COPD), and subsequent improvement in quality of life, decreased dyspnea and lower risk of hospitalization (8). To a lesser extent, work is being carried out on the value of a prehabilitation program in preparation for pulmonary surgery with a view to improving physical fitness and limiting postoperative respiratory disability (9). The review published by Nagarajan et al concluded that prehabilitation (PR) for pulmonary surgery improved exercise functional capacity and limited postoperative lung capacity reduction (10).…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20] Additionally, operations may be possible after pulmonary rehabilitation in patients who were inoperable due to the limited exercise capacity. [21] Despite the growing awareness of the importance of exercise training in the preoperative period, it is not realistic to include all patients in an exercise training in the clinical setting. Physiotherapists in the thoracic surgery department should, therefore, develop exercise prescriptions which are simple and cost-effective, and which are arranged according to the needs of the individuals considering its clinical benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Fizyoterapi rehabilitasyon yaklaşımlarını araştıran çalışmalar, erken rehabilitasyon ve ameliyat sonrası komplikasyonları önlemeye yönelik koruyucu fizyoterapi rehabilitasyon tekniklerini içeren çalışmalardır (22). Diğerleri ise cerrahi girişime uygun olan hastalarda ameliyat öncesi (23)(24)(25)(26)(27), ya da sonrası dönemde egzersiz eğitiminin ön planda olduğu araştırmalardır (14,(28)(29)(30)(31). Birkaçında ileri evre akciğer kanserinde hastane içi PR uygulamaları da yapılmıştır (32)(33)(34).…”
Section: Introductionunclassified
“…Birkaçında ileri evre akciğer kanserinde hastane içi PR uygulamaları da yapılmıştır (32)(33)(34). Bu araştırmaların hiçbirinde kontrol grubu yoktur (14,(23)(24)(25)(26)(27)(28)(29)(30)(31). Hasta sayıları azdır (24,25,27,28,(30)(31)(32)34).…”
Section: Introductionunclassified
See 1 more Smart Citation